Proposal and numerical feasibility study of a novel multi-modal and multi-axis dynamic vibration absorber consists of spherical viscoelastic material containing embedded ball-like mass - Takahiro TOMIOKA (The Japan Society of Mechanical Engineers, 2021)
This paper proposes a novel DVA (Dynamic Vibration Absorber) consisting of a ball-like mass embedded in a spherical viscoelastic material to meet practical demands for the multi-modal and multi-axis vibration reduction against elastic vibrations of structures. This DVA is called eMDVA (embedded Mass DVA) here, and the embedded mass can vibrate every direction in the viscoelastic medium. The unique concept of the eMDVA is inspired by the damping effect caused by passengers on railway vehicles. This paper describes a basic configuration of the eMDVA and some numerical studies using finite element (FE) vibration analysis to design the eMDVA. From the numerical investigation, it has been found that the natural frequency of a single-mass eMDVA can be controlled by changing the combination of the sizes of the viscoelastic sphere and the embedded mass. The frequency response function (FRF) of the acceleration of the embedded mass versus excitation force has a dominant single peak corresponding to one of the natural frequencies. These results indicate that the proposed eMDVA is suitable as a DVA, and it can be designed to tune the target vibration frequencies of host structures. As a more realistic analysis, numerical investigation for the thin and long plate-like host structure (a 1:10 scale model of the floor structure of a railway vehicle) was conducted, and multi-modal vibration reduction has been observed by applying the eMDVA consisting of two sets of viscoelastic spheres and embedded masses with different sizes. From these numerical investigations, it has been shown that the proposed eMDVA has promising potential as a multi-modal damper for elastic vibrations.